Morphological Changes of Anterior Cerebral Artery (ACA) in Hydrocephalic Pediatric Patients - Ozturk, Sait; Ayan, Erdogan; Kaplan, Metin (Iranian Child Neurology Soc, 2017)
Objective The morphology of anterior cerebral artery (ACA) in patients with hydrocephalus (HCP) was analyzed, and its importance was discussed in maintaining cerebral perfusion. Materials & Methods A total of 84 cases in 2 groups between 0 and 3 months, followed-up at Firat Universitesi Hastanesi, Beyin Cerrahisi Klinigi, Elazig, Turkiye due to in 2010-2013, were enrolled. Two groups were created for the study. Group 1; patients with HCP and Group 2; as control group without HCP. In both groups, the length of the A2 segment of ACA was measured from its origin to the junction of the genu and body portions of the corpus callosum on T2 mid-sagittal magnetic resonance (MR) scans. For all cases, axial MR imaging scans were used to calculate Evans' index (EI), and the cases were divided into three groups: Group A, EI >= 50%; Group B, EI of 40-50% and Group C, EI < 40%. The two groups (Groups 1 and 2) were compared with respect to ACA length, and the correlation with the EI was quantified. P values below 0.05 were considered statistically significant. Results Mean length of ACA was 57.3 mm in Group 1 and 37.5 mm in Group 2. EI increased as the length of ACA increased. A statistical comparison of the two groups revealed that the ACA length was significantly greater in Group 1. The relationship between EI and ACA length was statistically significant. Conclusion Reducing ventricular size appears to be an important factor in addition to reducing intracranial pressure in an attempt to maintain normal cerebral perfusion(CP).
Keywords: Anterior cerebral artery; Cerebral perfusion; Evans' Index; Hydrocephalus